2021
DOI: 10.3390/ijms22136655
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis of Beneficial Rhizobacteria to Root Exudates: The First Step towards Root–Microbe Rhizosphere Interactions

Abstract: Chemotaxis, the ability of motile bacteria to direct their movement in gradients of attractants and repellents, plays an important role during the rhizosphere colonization by rhizobacteria. The rhizosphere is a unique niche for plant–microbe interactions. Root exudates are highly complex mixtures of chemoeffectors composed of hundreds of different compounds. Chemotaxis towards root exudates initiates rhizobacteria recruitment and the establishment of bacteria–root interactions. Over the last years, important p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(42 citation statements)
references
References 90 publications
0
42
0
Order By: Relevance
“…Of the five isolates tested, two (n00163 and n00167) shared similar phenotypic carbon source usage characteristics (Table S8). Of the different metabolic phenotypes, methyl pyruvate is a plant chemoeffector ( 31 ) and glycerol is a leaf exudate as a result of carbon dioxide fixation in photosynthesis ( 32 ). Glycerol was not used by n00132, while methyl pyruvate was not used by n00132 and n00172.…”
Section: Resultsmentioning
confidence: 99%
“…Of the five isolates tested, two (n00163 and n00167) shared similar phenotypic carbon source usage characteristics (Table S8). Of the different metabolic phenotypes, methyl pyruvate is a plant chemoeffector ( 31 ) and glycerol is a leaf exudate as a result of carbon dioxide fixation in photosynthesis ( 32 ). Glycerol was not used by n00132, while methyl pyruvate was not used by n00132 and n00172.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that microorganisms with the ability to sense and uptake these substances with small molecular weight might be competent in the rhizosphere. Indeed, wide taxa of rhizosphere bacteria such as Pseudomonas and Bacillus can sense carboxylic acids and amino acids, which may stimulate bacterial mobility ( Taguchi et al, 1997 ; Alvarez-Ortega and Harwood, 2007 ; Sampedro et al, 2015 ; Feng et al, 2021 ). An increase of functional traits associated with amino acid competition indicated a fascinating relationship between plant and rhizosphere microorganisms in terms of N-exchanging.…”
Section: Discussionmentioning
confidence: 99%
“…Root exudates modulate the composition of the microbial community in the rhizosphere, i.e., the soil influenced by plant roots [103,104]. The persistence of a bacterial population in the rhizosphere depends in part on its chemotaxis toward different components secreted by the roots as well as its ability to use them as substrates [105][106][107][108]. The possibility of moving in the soil, and thus the presence of flagella in bacterial species, are characteristics necessary to reach the root and, therefore, influence the nodulation [109].…”
Section: Bacterial Survival In the Rhizospherementioning
confidence: 99%